Feeding microalgae meal (All-G Rich (TM); Schizochytrium limacinum CCAP 4087/2) to beef heifers. I: Effects on longissimus lumborum steak color and palatibility - Phelps, Kelsey J.; Drouillard, James S.; O'Quinn, Travis; Burnett, D. D.; Blackmon, Terri L.; Axman, J. E.; Van Bibber-Krueger, Cadra L.; Gonzalez, John M. (My University, 2017)
The objective of this study was to examine effects of 4 levels of microalgae meal (All-G Rich, Schizochytrium limacinum CCAP 4087/2; Alltech Inc., Nicholasville, KY) supplementation to the diet of finishing heifers on longissimus lumborum (LL) steak PUFA content, beef palatability, and color stability. Crossbred heifers (n = 288; 452 +/- 23 kg initial BW) were allocated to pens (36 pens and 8 heifers/ pen), stratified by initial pen BW (3,612 +/- 177 kg), and randomly assigned within strata to 1 of 4 treatments: 0, 50, 100, and 150 g . heifer(-1) . d(-1) of microalgae meal. After 89 d of feeding, cattle were harvested and LL were collected for determination of fatty acid composition and Warner-Bratzler shear force (WBSF), trained sensory panel evaluation, and 7-d retail color stability and lipid oxidation analyses. Feeding microalgae meal to heifers increased (quadratic, P < 0.01) the content of 22: 6n-3 and increased (linear, P < 0.01) the content of 20: 5n-3. Feeding increasing levels of microalgae meal did not impact total SFA or MUFA (P > 0.25) but tended (P = 0.10) to increase total PUFA in a quadratic manner (P = 0.03). Total omega-6 PUFA decreased (linear, P = 0.01) and total omega-3 PUFA increased (quadratic, P < 0.01) as microalgae meal level increased in the diet, which caused a decrease (quadratic, P < 0.01) in the omega-6: omega-3 fatty acid ratio. Feeding microalgae meal did not affect WBSF values or sensory panel evaluation of tenderness, juiciness, or beef flavor scores (P > 0.16); however, off-flavor intensity increased with increasing concentration of microalgae meal in the diet (quadratic, P < 0.01). From d 5 through 7 of retail display, steaks from heifers fed microalgae meal had a reduced a* value and oxymyoglobin surface percentage, with simultaneous increased surface metmyoglobin formation (quadratic, P < 0.01). Lipid oxidation analysis indicated that at d 0 and 7 of display, as the concentration of microalgae meal increased in the diet, the level of oxidation increased (quadratic, P < 0.01). Muscle fiber type percentage or size was not influenced by the inclusion of microalgae meal in diets (P > 0.19); therefore, the negative effects of microalgae on color stability were not due to fiber metabolism differences. Feeding microalgae meal to finishing heifers improves PUFA content of beef within the LL, but there are adverse effects on flavor and color stability.
Citation: Phelps, K. J., Drouillard, J. S., O'Quinn, T. G., Burnett, D. D., Blackmon, T. L., Axman, J. E., . . . Gonzalez, J. M. (2016). Feeding microalgae meal (All-G Rich (TM); Schizochytrium limacinum CCAP 4087/2) to beef heifers. I: Effects on longissimus lumborum steak color and palatibility. Journal of Animal Science, 94(9), 4016-4029. doi:10.2527/jas2016-0487
Keywords: Color; Fatty Acid; Longissimus Lumborum; Microalgae; Palatability; Fatty-Acid-Composition